The Use of Dialogue Journals in an ESL Writing Class from Vygotskyan Perspective - Rana, Lal Bahadur (Journal of NELTA Surkhet, 2018)
Dialogue journal writing is a way of communicating with the learners through constant written communication over a specified period. Since the teachers who use the dialogue journals do not require their students to be grammatically accurate in their expressions while they are writing journals, the students build their self-confidence. Consequently, they can increase their writing fluency, which ultimately leads to not only the development of writing but also overall language proficiency of the language they are learning. More importantly, it develops learners’ theoretical thinking as they are involved in dialogic discussions through written interactive communications. It is because as per Vygotskyan theory of human development human beings are constantly engaged in interpersonal as well as intrapersonal communications, which expand learners’ zones of proximal development.Journal of NELTA Surkhet Vol. 5 January, 2018, Page: 1-14